Effects of internet addiction and academic satisfaction on mental health among college students after the lifting of COVID-19 restrictions in China - Deng, Ai-Ping; Wang, Cong; Cai, Jia; Deng, Zhong-Yue; Mu, Yun-Fei; Song, Hong-Jun; Meng, Ya-Jing; Meng, Xian-Dong; Huang, Xue-Hua; Zhang, Lan; Huang, Yi; Zhang, Wei; et al. (Frontiers in Psychiatry, 2023)
Internet addiction (IA) among students, worsened by Coronavirus disease 2019 (COVID-19) pandemic, has become a social problem with the digitalization of school learning and many aspects of daily life. However, few studies on IA have been conducted among students after the lifting of COVID-19 restrictions in China.This large-sample, cross-sectional, online survey was conducted to explore the characteristics of IA and the association among IA, academic satisfaction, and mental health problems from December 14, 2022 to February 28, 2023 in Sichuan, China. All participants (N=22605) were students in colleges and universities, recruited via their teachers and professors.Of all the participants, 14921 (66.0%) participants had IA. Participants with IA were more likely to have depression symptom, anxiety symptom, insomnia, and lifetime suicidal ideation. In addition, participants with severe IA had significantly higher rates of mental health problems (e.g., depression, anxiety, insomnia, and suicidal ideation) than those with mild IA. A significant IA-by-academic satisfactory-interaction on mental health was identified: participants with higher level of IA showed particularly severe symptom of depression, anxiety and insomnia when affected by low satisfactory of academy (p<0.001).This study reveals that IA has a significantly negative impact on mental health among college students after the lifting of COVID-19 restrictions in China. IA and academic satisfaction have interactive impacts on mental health problems among students.Further educational and health policies and psychosocial interventions should be developed to reduce IA and enhance academic satisfaction for improving students' mental health.